-.111(x-27)+.333(x+3)=x+67

Simple and best practice solution for -.111(x-27)+.333(x+3)=x+67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -.111(x-27)+.333(x+3)=x+67 equation:


Simplifying
-0.111(x + -27) + 0.333(x + 3) = x + 67

Reorder the terms:
-0.111(-27 + x) + 0.333(x + 3) = x + 67
(-27 * -0.111 + x * -0.111) + 0.333(x + 3) = x + 67
(2.997 + -0.111x) + 0.333(x + 3) = x + 67

Reorder the terms:
2.997 + -0.111x + 0.333(3 + x) = x + 67
2.997 + -0.111x + (3 * 0.333 + x * 0.333) = x + 67
2.997 + -0.111x + (0.999 + 0.333x) = x + 67

Reorder the terms:
2.997 + 0.999 + -0.111x + 0.333x = x + 67

Combine like terms: 2.997 + 0.999 = 3.996
3.996 + -0.111x + 0.333x = x + 67

Combine like terms: -0.111x + 0.333x = 0.222x
3.996 + 0.222x = x + 67

Reorder the terms:
3.996 + 0.222x = 67 + x

Solving
3.996 + 0.222x = 67 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
3.996 + 0.222x + -1x = 67 + x + -1x

Combine like terms: 0.222x + -1x = -0.778x
3.996 + -0.778x = 67 + x + -1x

Combine like terms: x + -1x = 0
3.996 + -0.778x = 67 + 0
3.996 + -0.778x = 67

Add '-3.996' to each side of the equation.
3.996 + -3.996 + -0.778x = 67 + -3.996

Combine like terms: 3.996 + -3.996 = 0.000
0.000 + -0.778x = 67 + -3.996
-0.778x = 67 + -3.996

Combine like terms: 67 + -3.996 = 63.004
-0.778x = 63.004

Divide each side by '-0.778'.
x = -80.98200514

Simplifying
x = -80.98200514

See similar equations:

| -2+10=24 | | 8z+12z=112 | | 134=x+2x+(x+18) | | 12+2/3(x-9)=0 | | 8x+5=4(5)+4 | | (-6y-8z)(-4)= | | -(5y+5)-(-4y-7)=-6 | | 8z+10=180 | | x-7.8=-5.9 | | -6/7+2/3=y | | -4(3a-2)-2(r+1)= | | 786=x+34+4x-40 | | X/18=-17 | | 8-5x+11+2x+4x-2=22 | | 6(t-5)+6t=4(3t+4)-11 | | 3.5(x+1.4y)+4(1.4x+1.3y)= | | 5+3s-2=8s+3-4s | | (3x+19/5)+(x+47/6)=17 | | (2/17)x=10 | | 3x-3.5=6.4x-16.42 | | 2t+7t=45 | | 7.79=2(3.14*r) | | (8-5i)(8-5i)= | | -(5y+5)-(-4y-6)=-3 | | 7.3x-8=6.3x+1 | | y/20=-26 | | 3(2x-1)+5=13 | | a=1/2(18*24) | | 1/6x=39 | | 17-3x=2x-2 | | 786=x+34+4(x-40) | | 8x5/9 |

Equations solver categories